1993
DOI: 10.1262/jrd.39.229
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Plasma Cortisol, Luteinizing Hormone (LH), Growth Hormone (GH) and Insulin-Like Growth Factor 1 (IGF 1 ) Concentrations in Clenbuterol Treated Veal Calves.

Abstract: The possible influence of a ƒÀ-adrenergic agonist, Clenbuterol, on GH, IGF-1, LH and cortisol secretion was investigated in young female calves. Clenbuterol (5 ƒÊg/kg liveweight) was fed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…It is not surprising that the beta-agonist was not found to be immunosuppressive in the present study, as cortisol was not elevated by the beta-agonist. This is consistent with previous studies that reported that betaagonists do not affect cortisol concentration in lambs and calves under conventional conditions (Beermann et al 1987;Chikhou et al 1991;Sauerwein et al 1993). Although it was reported that clenbuterol suppressed humoral immunological function in lambs (Spencer and Oliver 1996), our results indicate that L-644,969 did not affect cellmediated immune response in terms of leukocyte profile and lymphocyte function.…”
Section: Discussionsupporting
confidence: 93%
“…It is not surprising that the beta-agonist was not found to be immunosuppressive in the present study, as cortisol was not elevated by the beta-agonist. This is consistent with previous studies that reported that betaagonists do not affect cortisol concentration in lambs and calves under conventional conditions (Beermann et al 1987;Chikhou et al 1991;Sauerwein et al 1993). Although it was reported that clenbuterol suppressed humoral immunological function in lambs (Spencer and Oliver 1996), our results indicate that L-644,969 did not affect cellmediated immune response in terms of leukocyte profile and lymphocyte function.…”
Section: Discussionsupporting
confidence: 93%